IMPROVEMENT OF SOCIAL SKILLS IN COOPERATION THROUGH APPLICATION OF MODEL PROBLEM-BASED LEARNING (PBL) ON IPS LEARNING IN BASIC SCHOOL - Rusaman, Sally Oktavianty; Harviansyah, Dina; Arga, Hana Sakura Putu (COLLASE (Creative of Learning Students Elementary Education), 2018)
This research was carried out at SDN 035 Soka Bandung City with the subjects of the fourth grade student participants totaling 30 people, this research was motivated by the phenomena that occur in elementary school students in teaching and learning activities that are lacking in collaboration with friends, very visible in learning activities when The teacher forms a discussion group to do group assignments, it seems that there are only a few group members who work while the other members seem indifferent to their assignments. Thus, there needs to be a problem solving that must be done to improve student collaboration in social studies learning, namely by applying the learning model of Problem Based Learning. The research method used was PTK with the Kemmis and Taggart models. Data collection techniques use observation, tests, documentation and field notes. The results of the study showed that the application of the Problem Based Learning model in social studies learning could improve cooperation among students. This can be seen from the percentage of the components of the formation of cooperation both from the aspect of knowledge and awareness that increases in each cycle.